Do you speak cat? Assessing the impact of a training video on human recognition of cat emotions and behaviours during play interactions - Henning, Julia S. L.; Nielsen, Torben; Hazel, Susan; Atkinson, Peter J. (Frontiers in Ethology, 2025)
Human-cat interactions require accurate interpretation of cat behavioural cues to ensure welfare and safety for both species. Misinterpretation of cat communications during play can lead to unwanted interactions that prolong stress for cats and increase the risk of human injury. A survey investigated factors associated with human ability to recognize cat emotional valence during human-cat ‘play’ interactions and a randomized controlled trial assessed the effectiveness of an educational training video. Participants were randomized to receive either a training video on cat play cues or a control video. A total of 368 adult participants within Australia categorized cat behaviours in videos of human-cat interactions as positive or negative. Novel use of a hierarchical summary receiver operating characteristic (HSROC) framework was used to assess participant accuracy. Results showed that participants were generally accurate when recognizing overt cat behaviours but performed at levels approximating chance when recognizing subtle negative cues. Previous vocational cat experience was associated with higher accuracy in negative interactions. Training had a small but significant positive impact on overall performance but paradoxically significantly decreased subtle negative behaviour recognition. On average, one in four cats in an overtly negative state were misclassified by participants. Even when valence was correctly recognized, a concerning proportion of participants still selected that they would engage in high-risk interactions with a cat in a negative state. Brief educational interventions may be insufficient or counterproductive for teaching subtle cue recognition in cats, highlighting a need for more comprehensive training approaches that prioritize early stress signals and appropriate response strategies. When promoting human-cat play interactions, care should be taken to ensure guardians are able to recognize when their cat does not wish to play and understand how to correctly respond to cats in a negative state.